2019
DOI: 10.1186/s40709-019-0105-y
|View full text |Cite
|
Sign up to set email alerts
|

Polyphasic taxonomy of green algae strains isolated from Mediterranean freshwaters

Abstract: BackgroundTerrestrial, freshwater and marine green algae constitute the large and morphologically diverse phylum of Chlorophyta, which gave rise to the core chlorophytes. Chlorophyta are abundant and diverse in freshwater environments where sometimes they form nuisance blooms under eutrophication conditions. The phylogenetic relationships among core chlorophyte clades (Chlorodendrophyceae, Ulvophyceae, Trebouxiophyceae and Chlorophyceae), are of particular interest as it is a species-rich phylum with ecologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Features such as cell shape and arrangement, location of pyrenoid, characteristic spines on the cell surface were all used for the preliminary identification of the strains. Reference was made to microscopic images of strains available in the literature [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Features such as cell shape and arrangement, location of pyrenoid, characteristic spines on the cell surface were all used for the preliminary identification of the strains. Reference was made to microscopic images of strains available in the literature [ 17 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…They are all found in freshwater systems from different geographic regions, and their sequences match previously published sequences. Scenedesmaceae and Chlorella strains have been found to be the most common aquatic algae isolated from the aquatic systems sampled in our study, as they are the most commonly reported genera of freshwater coccoid green algae with a ubiquitous distribution [33,39]. Some of these species, like Tetradesmus dimorphus, Coelastrella sp., Chlorella vulgaris and C. sorokiniana, have been found throughout the Andean region and present no variability in the barcode sequences.…”
Section: Discussionmentioning
confidence: 74%
“…The V4 18S rDNA region is considered suitable for molecular analysis due to its greater size and variability of inversions, insertions, and deletions [36,37]. Another promising candidate is the rbcL marker; despite the lack of a universal primer pair for successful rbcL amplification, it is reportedly sufficiently variable to be able to distinguish among most chlorophyte species [18,38,39]. In fact, there are currently c. 9,000 rbcL sequences from chlorophyte species deposited in the DDBJ/EMBL/GenBank database.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior is explained by the size of these microorganisms: while the size of Tetraselmis sp. ranges from 10-25 µm long and 7-20 µm wide [39], D. subspicatus has roughly half that size, ranging from 5-13 μm long and 3-7 µm wide [40]. This cell size difference can be visualized in Figures 1b and 1c.…”
Section: Relationship Between Numbers Of Cells Per ML and Optical Den...mentioning
confidence: 88%